Influence of perceived and preferred coach feedback on youth athletes' perceptions of team motivational climate - Stein, J.; Bloom, G. A.; Sabiston, C. M. (Psychology of Sport and Exercise, 2012)
Objectives: This study examined youth ice hockey players' perceptions of individual feedback received from their coach, and the agreement and discrepancies between preferred and perceived coach feedback patterns, on athletes' perceptions of team motivational climate. The following research questions were answered: How does agreement in perceived and preferred coach feedback relate to task- and ego-involving motivational climate? Design: This study used non-probability based sampling within a cross-sectional (survey) design. Method: Athletes (n = 70) completed a self-report survey comprised of measures of coaching feedback and motivational climate. The data were examined using polynomial regression and response surface analysis. Results: Linear associations were observed between coaching feedback and motivational climate, and unique associations between the perceived and preferred coach feedback discrepancies were distinctly related to increased perceptions of both task- and ego-involved motivational climates. Conclusions: The type of feedback, purpose of the feedback, and agreement or discrepancy in perceptions and preferences for different feedback styles are important to understanding task- and ego-involved motivational climate in youth sport. Coaching programs should assist coaches in learning their athletes' preferences for positive and negative feedback in sport and matching these preferences with their individual feedback styles.